2020
DOI: 10.1534/genetics.120.303270
|View full text |Cite
|
Sign up to set email alerts
|

A Transcriptional Regulatory Map of Iron Homeostasis Reveals a New Control Circuit for Capsule Formation in Cryptococcus neoformans

Abstract: Iron is essential for the growth of the human fungal pathogen Cryptococcus neoformans within the vertebrate host, and iron sensing contributes to the elaboration of key virulence factors, including the formation of the polysaccharide capsule. C. neoformans employs sophisticated iron acquisition and utilization systems governed by the transcription factors Cir1 and HapX. However, the details of the transcriptional regulatory networks that are governed by these transcription factors and connections to virulence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
37
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(44 citation statements)
references
References 84 publications
7
37
0
Order By: Relevance
“…Under high-iron conditions, Cir1 is more abundant, and the protein acts as a repressor for genes, including those involved in iron uptake and metabolism. In contrast, HapX mainly acts as a repressor under low-iron conditions to inhibit the expression of genes involved in iron-consuming functions [ 36 ]. In the current study, we found that the protein levels of both Cir1 and HapX were significantly reduced in the sod2 mutant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Under high-iron conditions, Cir1 is more abundant, and the protein acts as a repressor for genes, including those involved in iron uptake and metabolism. In contrast, HapX mainly acts as a repressor under low-iron conditions to inhibit the expression of genes involved in iron-consuming functions [ 36 ]. In the current study, we found that the protein levels of both Cir1 and HapX were significantly reduced in the sod2 mutant.…”
Section: Discussionmentioning
confidence: 99%
“…In mammalian cells, overexpression of mitochondrial Mn-SOD significantly reduced non-heme iron levels, which is in agreement with our data [ 37 , 38 ]. We hypothesize that increased superoxide due to lack of Sod2 may also cause a reduction in the stability and activity of Cir1 and HapX since the proteins are predicted to contain Fe-S clusters and iron influences their stability [ 21 , 36 ]. Indeed, previous studies have reported that superoxide causes the release of iron from the Fe-S cluster and in turn inactivates the Fe-S cluster-containing protein [ 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, hapX and cir1 , a homologue of sreA , in Cryptococcus neoformans have been extensively studied in relation to virulence in humans [ 12 , 13 ]. Similar to the ascomycetes, hapX in C. neoformans represses iron utilization and promotes iron uptake and cir1 expression under iron starvation conditions [ 12 , 13 ]. Therefore, the deprivation of iron is a prerequisite for the expression of hapX and thus for the production of siderophore in fungi.…”
Section: Introductionmentioning
confidence: 99%
“…Upon iron deprivation, the HapX-CBC complex acts as a repressor of genes involved in irondependent pathways, i.e. genes encoding iron-sulfur cluster and heme containing proteins or involved in the biogenesis and assembly of these two prosthetic groups, and genes encoding transporters responsible for vacuolar sequestration of iron (Hortschansky et al, 2007;Jung et al, 2010;Singh et al, 2011;Lopez-Berges et al, 2012;Kröber et al, 2016;Wang et al, 2019;Do et al, 2020). In the human and plant pathogens Aspergillus fumigatus, Fusarium oxysporum and Verticillium Dahliae, HapX is also responsible for the induction of some of these "iron consuming genes" in high iron conditions, therefore playing a key role in iron tolerance (Gsaller et al, 2014;Wang et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…HapX and its orthologues are transcriptionally induced by iron starvation and sense iron through conserved cysteine rich domains (CRD) in their C-terminal part (Hortschansky et al, 2007;Schrettl et al, 2010;Hsu et al, 2011;Singh et al, 2011;Lopez-Berges et al, 2012;Gsaller et al, 2014;Rietzschel et al, 2015;Kröber et al, 2016;Do et al, 2020). Importantly, HapX also contains a basic leucine zipper (bZIP) domain and belongs to the Yeast AP-1 (YAP) family of specific DNA binding transcriptional regulators (Tanaka et al, 2002;Singh et al, 2011;Rodrigues-Pousada et al, 2019).…”
Section: Introductionmentioning
confidence: 99%